A generic database adapter for multi-tier CORBA-based applications. - Cocard, Remus. (University of Ottawa (Canada), 2002)
This thesis presents a generic solution to the problem of database adapters for multi-tier CORBA based applications. This solution is based on the concept of metatype classes, which provide information about the types of objects that are being stored in a database. The concept of a metaobject protocol is introduced and discussed. The Database Adapter is proposed as a generic solution for managing persistent information for multi-tier CORBA based applications. A framework for developing multi-tier applications using a generic adapter is presented. A test application is developed to evaluate the management of objects and to measure the impact on performance. It is found that the ability to manage objects through the use of a generic adapter, without modifying the adapter when managing different new types of objects, results in only a slight increase in operation invocation time, but results in huge savings in development and testing time.
Keywords: Computer Science.